Fault lines in global Jihad : organizational, strategic and ideological fissures - Moghadam, Assaf, 1974-; Fishman, Brian (Milton Park, Abingdon, Oxon : Routledge, 2011)
'This book is a detailed discussion of the internal problems and weaknesses of the global jihad movement led by Al-Qaeda'--
Includes bibliographical references (p. [256]-257) and index.
Keywords: Qaida (Organization); Jihad; Islamic fundamentalism; Terrorism -- Religious aspects -- Islam; World politics -- 21st century